2014
DOI: 10.12973/eurasia.2014.1060a
|View full text |Cite
|
Sign up to set email alerts
|

Turkish, Indian, and American Chemistry Textbooks Use of Inscriptions to Represent ‘Types of Chemical Reactions’

Abstract: The purpose of this study was to investigate inscriptions used in "Types of chemical reactions" topic in Turkish, Indian, and American chemistry textbooks. We investigated both the types of inscriptions and how they were used in textbooks to support learning. A conceptual analysis method was employed to determine how those textbooks use inscriptions to present "Types of chemical reactions." Results revealed that textbooks disproportionately used inscriptions at symbolic level and failed to present submicroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…We also captured the theoretical and/or analytical frameworks that were used to analyze chemistry textbooks or design studies around chemistry textbooks . Several frameworks were used in multiple studies that employed theoretical frameworks: Johnstone’s Triangle, ,,,,,,,,, Cognitive Load Theory, ,, Bloom’s Taxonomy, ,, Mayer’s Multimedia Principles, , Ainsworth’s Design, Functions, Tasks (DeFT) Framework, , Robert’s Curriculum Emphases, , and the Framework on Scientific Literacy. , We identified multiple other frameworks that were each used in a single study on chemistry textbooks (e.g., the Information Processing Model, Vygotsky’s Zone of Proximal Development, Kozma and Russel’s Representational Competence, Fink’s Taxonomy of Significant Learning, Han and Roth’s Semiotic Model, Vermunt and Verloop’s Taxonomy of Learning Activities, Wu and Shah’s Five Principles of Textual Diagrams, Constructivism, the Analogy Classification Framework, Bunge’s Five Ontological Categories, Ausubel and Novak’s Meaningful Learning, and others). Importantly, about half of the articles ( n = 39, 49%) did not use any theoretical/analytical frameworks to guide the design of their studies and the interpretation of their findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also captured the theoretical and/or analytical frameworks that were used to analyze chemistry textbooks or design studies around chemistry textbooks . Several frameworks were used in multiple studies that employed theoretical frameworks: Johnstone’s Triangle, ,,,,,,,,, Cognitive Load Theory, ,, Bloom’s Taxonomy, ,, Mayer’s Multimedia Principles, , Ainsworth’s Design, Functions, Tasks (DeFT) Framework, , Robert’s Curriculum Emphases, , and the Framework on Scientific Literacy. , We identified multiple other frameworks that were each used in a single study on chemistry textbooks (e.g., the Information Processing Model, Vygotsky’s Zone of Proximal Development, Kozma and Russel’s Representational Competence, Fink’s Taxonomy of Significant Learning, Han and Roth’s Semiotic Model, Vermunt and Verloop’s Taxonomy of Learning Activities, Wu and Shah’s Five Principles of Textual Diagrams, Constructivism, the Analogy Classification Framework, Bunge’s Five Ontological Categories, Ausubel and Novak’s Meaningful Learning, and others). Importantly, about half of the articles ( n = 39, 49%) did not use any theoretical/analytical frameworks to guide the design of their studies and the interpretation of their findings.…”
Section: Resultsmentioning
confidence: 99%
“…Upon more in-depth screening of these articles, we excluded 4 that did not fit our inclusion criteria. The final sample included 79 studies. While we intend this review to be comprehensive, we acknowledge the possibility of unintentional omissions. Of note is that none of the articles in this review are written by the authors of this manuscript.…”
Section: Methodsmentioning
confidence: 99%
“…Given that we found inconsistencies in how organic chemistry textbooks teach RC skills across text, worked examples, and practice problems, and that these textbooks do not support students in developing metarepresentational competence, the instructors must be aware of the shortcomings of the textbooks that they select for their courses and use in developing their instructional materials. Other studies that analyzed other aspects of integrating representations in chemistry textbooks reported additional shortcomings that the teachers and instructors need to be aware of: (a) there is a high prevalence of decorative representations in some general chemistry textbooks, which might add to the extraneous cognitive load and likely take away from the cognitive resources devoted to learning; (b) there are inadequate connections between symbolic, macroscopic, and submicroscopic representations in some textbooks; (c) multiple studies identified problematic captions or missing captions in many general chemistry, physical chemistry, and secondary chemistry textbooks; , and (d) many representations in chemistry textbooks are not well-linked to text or other representations. ,,, For example, Nyachwaya and Gillaspie found that a considerable number of representations in general chemistry textbooks were separated by a whole page from the associated text . In summary, research shows that some chemistry textbooks lack an optimal design when incorporating representations.…”
Section: Discussion and Implications For Textbook Developers And Chem...mentioning
confidence: 99%
“…Since it is an aid primarily intended for students, the transmission of information remains its key role. Education process in general is largely conditioned by effective communication [12]. So, if a textbook is to fulfil its function as a medium, which enables the transmission of information to students, it is necessary to emphasise the quality of the text contained therein not only from the point of view of its content, despite its suitability and factual accuracy are an essential factor in education.…”
Section: Theoretical Backgroundmentioning
confidence: 99%